2023
DOI: 10.1080/15592294.2023.2199373
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially methylated genes for severe acne by genome-wide DNA methylation and gene expression analysis

Abstract: Severe acne is a chronic inflammatory skin condition that is affected by both genetic and environmental factors. DNA methylation is associated with a variety of inflammatory skin diseases, but its role in severe acne is unclear. In this study, we conducted a two-stage epigenome correlation study using 88 blood samples to identify disease-related differential methylation sites. We found close associations between the DNA methylation at 23 differentially methylated sites (DMSs) and severe acne, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They were detected using the Illumina Infinium Methylation EPIC BeadChip, which can quantitatively measure more than 865,911 methylation sites. We described the methylation assay for each sample in a previous study ( 15 ), from which we obtained 23 differentially methylated loci significantly associated with severe acne ( Supplementary Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were detected using the Illumina Infinium Methylation EPIC BeadChip, which can quantitatively measure more than 865,911 methylation sites. We described the methylation assay for each sample in a previous study ( 15 ), from which we obtained 23 differentially methylated loci significantly associated with severe acne ( Supplementary Table S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are still few studies on DNA methylation associated with severe acne, several inflammatory skin diseases, including psoriasis and systemic lupus erythematosus, have been found to be associated with DNA methylation, from which we infer that DNA methylation may play an influential role in the development of severe acne ( 13 , 14 ). A previous study identified 23 differentially methylated probes (DMPs) associated with severe acne ( 15 ). However, the potential mechanism by which these methylation markers are associated with severe acne is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation by AKT of the p53-binding factor MDM2 promotes p53 degradation, whereas isotretinoin treatment enhances the expression of p53, FoxO1 and FoxO3 in sebaceous glands of acne patients. A recent Chinese epigenetics study identified 23 differentially methylated sites related to severe acne, involving multiple genes such as PDGFD (platelet-derived growth factor D), ARHGEF10 (rho guanine nucleotide exchange factor 10), IL1R1 (IL-1 receptor), PARP8 (poly ADP-ribose polymerase 8), MAPKAPK2 (MAP kinase-activated protein kinase 2), MUC8 (mucin isoform secreted in the endometrium and endocervix), NAV1 (neuron navigator 1), KCNT2 (Na + -activated K + channel T2 or slick channel), and Wnt9A (an embryogenetic differentiation and patterning factor of the Wnt family) [72]. Another recent study performed a DNA methylation and multi-omics analysis of acne skin samples, finding 31,134 differentially methylated sites and 770 differentially methylated genes with changes in expression [73].…”
Section: Genetic Insights In Afa and Pcosmentioning
confidence: 99%
“…Advances in genomics and transcriptomics, alongside highthroughput sequencing technologies, have ushered in an era of in-depth exploration into the genetic landscape of acne. [12][13][14] The advent of recent advances in genomics, transcriptomics, and bioinformatics tools has enabled in-depth exploration into the genetic landscape of acne, emphasizing the role of differentially expressed genes (DEGs) in its pathology. [15][16][17] Such technological progress, particularly in transcriptomic analyses, offers a deeper understanding of the molecular and genetic landscapes of acne, potentially unveiling diagnostic markers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in genomics and transcriptomics, alongside high‐throughput sequencing technologies, have ushered in an era of in‐depth exploration into the genetic landscape of acne 12–14 . The advent of recent advances in genomics, transcriptomics, and bioinformatics tools has enabled in‐depth exploration into the genetic landscape of acne, emphasizing the role of differentially expressed genes (DEGs) in its pathology 15–17 .…”
Section: Introductionmentioning
confidence: 99%